Temporal relationship between atrial fibrillation and ischaemic stroke in a large cohort with continuous rhythm monitoring. (25th November 2020) - Singer, D; Ziegler, P.D; Koehler, J; Sarkar, S; Passman, R
Abstract: Background/Introduction: Atrial fibrillation (AF) increases the risk of ischaemic stroke, but the temporal relationship is uncertain. Purpose: To assess the temporal relationship between AF episodes and ischaemic stroke in patients with cardiovascular implantable electronic devices (CIED) utilizing a case-crossover analysis. Methods: We linked a very large U.S. aggregated de-identified electronic health record database (2007–2017), containing claims for ischaemic stroke hospitalizations, to a manufacturer's CIED database with continuous AF monitoring. All stroke patients with ≥120 days of pre-stroke rhythm data were included. For each stroke patient, we compared the presence of a day with ≥5.5 hours of AF (the TRENDS study threshold) in the case period (days 1–30 pre-stroke) to that in the control period (days 91–120 pre-stroke). Matched analyses for dichotomous outcomes generated odds ratios with confidence intervals and p values. Results: We identified 891 ischaemic stroke patients (71.3±10.5 years, 65% male, 27% pacemakers, 60% defibrillators, 13% insertable cardiac monitors) with continuous monitoring data in the 120 days pre-stroke. The vast majority had either no AF in both the case and control periods (n=682, 77%) or AF in both periods (n=143, 16%), i.e., non-informative records. However, among the 66 patients with informative, discordant arrhythmic states, 52 had AF in the case period versus 14 in the control period, for an odds ratio of 3.71 (95% C.I. 2.06–6.70, p<0.001). Analysed by 5-day periods, stroke risk was markedly increased within 30 days of the AF episode (figure). For days 1–5 following an AF episode, the odds ratio was 9.7 (95% C.I. 5.9–16.1). Risk diminished towards non-AF risk after 30 days. Conclusion: Our analysis of this largest cohort with continuous rhythm monitoring prior to ischaemic stroke demonstrates that stroke risk is highest within a few days of an episode of AF and diminishes rapidly thereafter. Our findings support a strategy of time-limited anticoagulation for patients with infrequent episodes of AF and available continuous rhythm monitoring. Funding Acknowledgement: Type of funding source: None